Peran Stakeholder dalam Pengembangan Tebu Rakyat (Studi pada Wilayah Kerja Pabrik Gula Redjosarie Kabupaten Magetan) - Tutik, Tutik (Jurnal Administrasi Publik, 2014)
Abstract: The Role of Stakeholder in The Development of Sugarcane (Studies on the Working Area of Redjosarie Sugar Factory in Magetan District. Achievement of national self-sufficiency in 2014 supported by the Technical Guidelines for Increased Production, Productivity, and Quality ofPlantsAnnuals who are composed by Ministryof Agriculture, which then translated back into the Implementation Guidelines and the Technical Guidelines through the Development of Sugarcane at the district/city level. Development of Sugarcane activities at the Magetan district level involving relevant stakeholders. The stakeholders have roles in the lending capital for sugar cane farmers, extension activities, Intersection Partnership Forum (FTK) activities, display gardens activities. The results showed that the stakeholders have performed its role well. The roles cause coordination and control between technical team from Estate Official of Magetan district and Redjosarie sugar factory, KPTR Sari Madu, and sugarcane farmers/farmer group.The method used is descriptive research with qualitative approach. Keyword: Development of Sugarcane, role, stakeholder and governance. Abstrak: Peran Stakeholder dalam Pengembangan Tebu Rakyat (Studi pada Wilayah Kerja Pabrik Gula Redjosarie Kabupaten Magetan). Pencapaian target swasembada gula nasional pada tahun 2014 oleh pemerintah didukung oleh Pedoman Teknis Peningkatan Produksi, Produktivitas, dan Mutu Tanaman Semusim yang disusun Kementrian Pertanian, yang selanjutnya dijabarkan kembali menjadi Petunjuk Pelaksanaan (Juklak) dan Petunjuk Teknis (Juknis) melalui Pengembangan Tebu Rakyat pada tingkat kabupaten/kota. Kegiatan Pengembangan Tebu Rakyat di Kabupaten Magetan melibatkan stakeholder terkait. Masing-masing stakeholder memiliki peran dalam kegiatan pemberian kredit modal kepada petani tebu, kegiatan penyuluhan, kegiatan Forum Temu Kemitraan, dan kegiatan kebun peraga. Hasil penelitian menunjukkan bahwa stakeholder telah menjalankan perannya dengan baik. Peran tersebut menimbulkan adanya koordinasi dan pengawasan antara Tim Teknis dari Dinas Perkebunan Kabupaten Magetan dan Pabrik Gula Redjosarie, Koperasi Petani Tebu Rakyat (KPTR) Sari Madu, dan petani tebu/kelompok tani. Metode penelitian yang digunakan adalah penelitian deskriptif dengan pendekatan kualitatif. Kata kunci: Pengembangan Tebu Rakyat, peran,stakeholder, dan governance.